Flexural strength of conventional flowable, bulk fill flowable and highly filled flowable resin composites: in vitro study. - Sulca Gonzales, Edith Liliana (2023)
Objective: To evaluate and compare the flexural strength of conventional flowable, bulk fill flowable and highly filled flowable resins. Materials and methods: Thirty 2mm x 2mm x 25mm specimens of Tetric N-Flow (TNF), Filtek Bulk Fill Flowable Restorative (FBF) and Beautifil Flow Plus F00 (BFP) flowable resins were made up; they were distributed into three groups according to brand (n=10) and stored in distilled water for 24 hours at 37ºC. The 3-point bending test according to ISO 4049 was performed on a universal testing machine at a speed of 0.5 mm/min until fracture. The results were evaluated with Anova and Tukey tests. P<0.05. Results: Statistically significant differences were found between the groups with a value of p=0.011. According to the statistical analysis, the groups that showed statistically significant differences were the BFP and TNF groups (p=0.015) and the BFP and FBF groups (p=0.035), while no statistically significant difference was found in the TNF and FBF groups. Conclusion: The high-filled flowable resin presents better flexural strength compared to the conventional flowable and bulk fill flowable resins, while the conventional and bulk fill flowable resins have no statistically significant difference.